ANALYSIS OF THE DETERMINANTS OF FOREIGN DEBT SUSTAINABILITY IN THE ASEAN REGION IN TERMS OF ISLAMIC ECONOMIC PERSPECTIVE (PANEL DATA ANALYSIS FOR THE PERIOD 2013-2022) - Sari Anastasya; Alief Rakhman Setyanto; Mia Selvina (International Conference on Humanity Education and Society (ICHES), 2024)
Foreign debt has become a phenomenon of financing funds sourced from abroad, without exception in the Asean (Association of Southeast Asian Nation) region, where these countries cooperate in the fields of socio-culture, politics, and economy. Apart from being a form of cooperative relationship, capital funding from abroad also plays an important role as a source of capital for countries that are carrying out economic development, including countries that have high natural resource potential and have a large population in the Asean region. There are several factors that can cause the amount of external debt to increase or decrease. In addition to economic growth and inflation, the exchange rate factor of a country's currency is also closely related to foreign debt. When there is a weakening of the exchange rate, foreign debt obligations also increase. The type of research used is quantitative research. The method used in this research is multiple regression with a panel data approach, the research period is from 2013 - 2022. The best model chosen uses the REM (Random Effect Model) model. The results showed that external debt is significantly affected by monetary policy in Asean countries. In terms of financing state development, external debt is viewed from two Islamic perspectives. The first view allows budget shortfalls to be covered through external financing that is customized and does not contradict sharia rules and principles.